Parameter Optimization Study of Ultra-High Speed Cutting by DOE Method - Li, Dongya; Jiang, Yichen; Wang, Shuang; Wu, Yifan (Manufacturing Technology Journal, 2024)
With the increasing demand for high-quality flange, there is a greater need for high-quality and high-speed machining technology. Aiming at the difficulty of surface roughness in meeting design requirements and poor machining stability of 7075 aluminum alloy, the classical Design of Experiments (DOE) method is employed to optimize the machining parameters and identify eight pertinent factors. By selecting the feed rate and cutting speed as the two significant factors, a mathematical model of roughness is derived, and the theoretically optimal machining parameters are determined. According to corresponding experimental results, the roughness, the parallelism of the two end faces of the flange, and machining efficiency, in order to further validate the accuracy of the model. The final processing parameters are 0.07 mm.r-1 feed rate and 1100 m.min-1 cutting speed, which provide a reference for actual production.
Keywords: Ultra-precision; DOE; Flange; Processing; Optimization study